Measurement development for eco-innovation capabilities of Malaysian oil and gas firms - Munodawafa, R.T. (Emerald Group Holdings Ltd., 2021)
Purpose: To combat concerns over the state of the natural environment, energy security and deteriorating air quality, the oil and gas sector needs to implement eco-innovations. Interest in eco-innovation is growing, as its implementation facilitates the transition toward sustainable development and a circular economy, while enabling firms to attain a competitive advantage vis-Ã -vis capabilities that foster sustainable economic and environmental development. However, literature on eco-innovation capabilities construct development, measurement and validation is scant. This study, therefore, develops an Eco-innovation Capabilities Scale for oil and gas firms. Design/methodology/approach: Three dimensions of Eco-innovation Capabilities are identified through an extensive literature review and qualitative interviews. Exploratory and Confirmatory Factor Analysis is applied to data collected from managers of Malaysian Oil and Gas Services and Equipment (OGSE) companies. Findings: Results reveal a parsimonious three-dimensional structure with nine items. The construct of eco-innovation capabilities is manifested by Product Service Stewardship, Environmental Pollution Prevention and Sustainable Development Commitment dimensions. Reliability analysis confirms the reliability and validity of the scale. Originality/value: The eco-innovation capabilities scale should be useful to researchers in exploring dimensions, factors and outcomes of eco-innovation capabilities. Oil and gas firms play a key role in the global energy mix; hence managers of oil and gas firms may also find this scale useful in measuring their eco-innovation implementation. Â© 2021, Emerald Publishing Limited.